2014
DOI: 10.4274/tjem.2441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Direct Medical Costs of Type 2 Diabetes Mellitus and its Complications in Turkey

Abstract: To estimate the direct annual medical costs of Type 2 diabetes and its complications in diagnosed patients in Turkey. Material and Method: A cost-of-illness model was developed. The prevalence of Type 2 diabetes was derived from the Turkish Diabetes Epidemiology Study, estimated as 13.7% in adults, with one-third of patients previously undiagnosed. Complication costs were extracted from the records of 7095 patients at a Turkish tertiary care hospital in 2009. For each modelled complication, acute phase costs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…A large proportion of this cost is related to hospitalization rates, which if reduced can sharply reduce the personal and socioeconomic burden due to diabetes 22. Similarly, in Turkey, management of diabetes-related complications accounted for more than half of the total cost associated with T2D 23. In this multinational survey, patients from Eurasia had a much higher prevalence of macrovascular and microvascular complications than other regions (47% and 87%, respectively).…”
Section: Discussionmentioning
confidence: 78%
“…A large proportion of this cost is related to hospitalization rates, which if reduced can sharply reduce the personal and socioeconomic burden due to diabetes 22. Similarly, in Turkey, management of diabetes-related complications accounted for more than half of the total cost associated with T2D 23. In this multinational survey, patients from Eurasia had a much higher prevalence of macrovascular and microvascular complications than other regions (47% and 87%, respectively).…”
Section: Discussionmentioning
confidence: 78%
“…These facts increase the significance of our present study. Previously, Malhan et al (6) conducted the largest cost effectiveness analysis of diabetes treatment in Turkey and exposed the total cost of diabetic complications. The total costs of complications of type 2 diabetes were estimated at between $3.93 and $4.44 billion and accounted for 1% of the gross domestic product (GDP).…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the Turkish patients with diabetes are aged between 40 and 64 years (2), and good glycemic control to reduce the risk of hypoglycemia is essential for the economic well-being of patients and their families. In 2010, it was estimated that the direct cost of managing major hypoglycemia in Turkey was 87 Turkish lira per acute episode (33). Patients have been demonstrated to increase blood glucose monitoring in response to hypoglycemic episodes (19), which may also increase costs associated with the management of hypoglycemia (26).…”
Section: Economic Impact Of Hypoglycemiamentioning
confidence: 99%
“…PREFER, a study comparing premixed insulin and basal-bolus regimens, demonstrated a lower incidence of severe hypoglycemia for premixed therapy, compared with the basal-bolus regimen, while the rates of non-severe hypoglycemia, weight gain, and nocturnal hypoglycemia were similar (42). In contrast, comparison of premixed insulins and basal insulin therapy demonstrated a higher overall risk of hypoglycemia with premixed insulin analogs (4,43).…”
Section: Economic Impact Of Hypoglycemiamentioning
confidence: 99%